Outcome of surgical resection for localized gastrointestinal stromal tumors - El-Badry, Ashraf M.; Ahmad, Medhat I. M.; Ali, Hitham M. (International Surgery Journal, 2016)
Background:Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors of the gastrointestinal tract. The clinical outcome and the factors which are potentially related to tumor recurrence and survival after surgical intervention for GISTs has not been adequately addressed in the Southern part of Egypt. Methods: Medical records of adult patients who underwent surgical resection of localized GISTs (February 2007 - December 2013) in Sohag University Hospital were reviewed. Data on the clinical presentation, treatment strategies, tumor characteristics including the risk for aggressive behavior and survival rate were analyzed. Results:Fifteen patients with 7 gastric (47%), 5 small bowel (33%), 2 duodenal (13%) and 1 colonic (7%) GISTs and median age of 56 (range: 32-73) years were eligible. Nine patients (60%) were males. Non-specific abdominal pain was the most common presenting symptoms (40%). Emergency presentation occurred only in two patients (13%). Complete resection was achieved in thirteen patients (87%). There was no major operative morbidity or mortality. The risk for aggressive behaviour was low in 7 (47%), intermediate in 5 (33%) and high in 3 (20%) patients. Two patients died 7 and 10 months after surgery, one with histopathological criteria of high risk for aggressive tumor behaviour and the other with incomplete tumor resection. During a median follow up of 21 (range: 8 - 48) months, overall and recurrence-free survival were 87% and 67%, respectively. Conclusions:Adequate resection of GISTs is associated with high rate of survival. Increased risk for aggressive tumor behaviour and incomplete resection are associated with tumor recurrence and decreased survival.